COMPONENTS OF COMPETENT TRAINING OF SCIENCE TEACHERS FOR SUCCESSFUL PROFESSIONAL ACTIVITIES - Novikova, T.; Manzii, O. (SWorld-Ger Conference proceedings, 2023)
The main components of professional competence are revealed in the article. The importance of possessing professional skills and abilities, modern special knowledge of a certain field of production and a high level of professional competence based on crit